MOLECULAR CHARACTERIZATION OF HAIRY FLEABANE USING RAPD - SILVA,D.R.O. (2016)
ABSTRACT With the increase of glyphosate resistance evolution in hairy fleabane, the knowledge of genetic diversity is essential to assist in the weed management. The objective was to characterize the genetic diversity of glyphosate resistant Conyza species in Rio Grande do Sul. Hairy fleabane biotype seeds were collected in fields of glyphosate-resistant soybean, generating seedlings used for extracting DNA from the leaves to perform a genetic diversity analysis, using the RAPD technique. The DNA was used in polymerase chain reaction and DNA fragments were assessed for polymorphism bands in electrophoresis. Biotypes were identified as Conyza bonariensis and microcephala varieties. In molecular analysis, among 25 primers RAPD, eight were reproducible generating polymorphisms of high intensity for the separation of biotypes. Cluster analysis revealed five groups, which had a genetic similarity of 53%. The results indicate that all known biotypes are of the same species, but exhibit different varieties. RAPD presents itself as an important tool for characterizing Conyza species.